2020
DOI: 10.1007/s11053-020-09712-5
|View full text |Cite
|
Sign up to set email alerts
|

Application of Low-Salinity Waterflooding in Carbonate Cores: A Geochemical Modeling Study

Abstract: Waterflooding is the most widely applied improved oil recovery technique. Recently, there has been growing interest in the chemistry and ionic composition of the injected water. Low-salinity waterflooding (LSWF) is a relatively recent enhanced oil recovery technique that has the ability to alter the crude oil/brine/rock interactions and improve oil recovery in both clastics and carbonates. In this paper, the increase in the recovery factor during LSWF was modeled based on the exchange of divalent cations (Ca2+… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 35 publications
2
10
0
Order By: Relevance
“…According to available sources, at least 50% of the primary oil is trapped in oil reservoirs after initial production and thus is not produced for various reasons. 1 The water injection method in secondary and tertiary recovery operations shows improved performance. 2 In the chemically improved water injection, dissolved components are engineered and managed to achieve the best performance in the presence of reservoir fluid and rock.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to available sources, at least 50% of the primary oil is trapped in oil reservoirs after initial production and thus is not produced for various reasons. 1 The water injection method in secondary and tertiary recovery operations shows improved performance. 2 In the chemically improved water injection, dissolved components are engineered and managed to achieve the best performance in the presence of reservoir fluid and rock.…”
Section: Introductionmentioning
confidence: 99%
“…According to available sources, at least 50% of the primary oil is trapped in oil reservoirs after initial production and thus is not produced for various reasons . The water injection method in secondary and tertiary recovery operations shows improved performance .…”
Section: Introductionmentioning
confidence: 99%
“…Reactive transport in porous media is commonly encountered in contaminant hydrology (MacQuarrie and Sudicky 1990), reactive flow in batteries and fuel cells (Gayon Lombardo et al 2019), nuclear waste disposal (Kenney et al 2017), oil recovery (Egbe et al 2021), carbon storage (Metz et al 2010), and chemical reactor engineering (Fogler 1987). In some applications, such as well stimulation by acidization, reaction is required, while in others, such as in dissolution-induced compromised well integrity, reaction is detrimental.…”
Section: Introductionmentioning
confidence: 99%
“…Sheng reviewed that approximately 17 mechanisms pertaining to solely LSWF, among which fine migration, mineral dissolution, Multicomponent Ion Exchange (MIE), and wettability alteration stood as prominent [22]. Extensive works [23][24][25][26] presented comprehensive results regarding the effects of ion types on the effectiveness of LSWF. They found that SO 4 2À is the most dominant in driving rock to less oil wetness.…”
Section: Introductionmentioning
confidence: 99%